Attrition of X chromosome inactivation in aged hematopoietic stem cells - Grigoryan, Ani; Pospiech, Johannes; Krämer, Stephen; Lipka, Daniel; Liehr, Thomas; Geiger, Hartmut; Kimura, Hiroshi; Medhanie Assmelash Mulaw; Florian, Maria Carolina (Stem cell reports, 2021)
During X chromosome inactivation (XCI), the inactive X chromosome (Xi) is recruited to the nuclear lamina at the nuclear periphery. Beside X chromosome reactivation resulting in a highly penetrant aging-like hematopoietic malignancy, little is known about XCI in aged hematopoietic stem cells (HSCs). Here, we demonstrate that LaminA/C defines a distinct repressive nuclear compartment for XCI in young HSCs, and its reduction in aged HSCs correlates with an impairment in the overall control of XCI. Integrated omics analyses reveal higher variation in gene expression, global hypomethylation, and significantly increased chromatin accessibility on the X chromosome (Chr X) in aged HSCs. In summary, our data support the role of LaminA/C in the establishment of a special repressive compartment for XCI in HSCs, which is impaired upon aging.